The sulphidization of mineral surfaces as applied to the froth flotation process - Ramagwede, Mudzimba Hubert (Rhodes University, Faculty of Science, Department of Chemistry, 1988)
This work constitutes a fundamental study of the interaction between soluble sulphide,copper (II) oxide and cerussite particles in the presence of CaÂ²â º ,MgÂ²â º starch , gum arabic and Triton X- IOO . A detailed investigation of the effect of pH of the system on the rate of sulphide uptake was made . In addition , the structural form of the surface precipitat.es were determined with the aid of scanning electron microscopy . On the basis of these results , it was concluded that adsorption of sulphide on cerussite in the presence or absence of CaÂ²â º starch, gum arabic and Triton X-IOO could either lead to the formation of a non-uniform or a uniform sulphide layer depending on the experimental conditions . However , the interaction of copper (II) Â· oxide wi th soluble sulphide in the presence or absence of the above mentioned species always led to the formation or a non-uniform sulphide layer . Preliminary experiments of the interaction between xanthate and sulphidized surface showed that oxide surface covered with metal sulphide layer reacts with less xanthate than the free oxide surface.
Keywords: Sulfide minerals; Flotation